2014
DOI: 10.1111/jdv.12359
|View full text |Cite
|
Sign up to set email alerts
|

Secukinumab improves hand, foot and nail lesions in moderate‐to‐severe plaque psoriasis: subanalysis of a randomized, double‐blind, placebo‐controlled, regimen‐finding phase 2 trial

Abstract: Secukinumab demonstrated a beneficial effect on psoriasis of the hands/feet/nails in this short-term assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
55
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(59 citation statements)
references
References 24 publications
3
55
0
1
Order By: Relevance
“…Other clinical trials and subanalyses confirmed the preliminary data about safety and efficacy of secukinumab both in the short-and long-term [75][76][77][78][79].…”
Section: Agents Targeting Il-17 (Secukinumab Brodalumab and Ixekizumab)supporting
confidence: 72%
“…Other clinical trials and subanalyses confirmed the preliminary data about safety and efficacy of secukinumab both in the short-and long-term [75][76][77][78][79].…”
Section: Agents Targeting Il-17 (Secukinumab Brodalumab and Ixekizumab)supporting
confidence: 72%
“…The effect of body weight on treatment response rates showed slightly higher PASI 75 responses in patients weighing less than 90 kg than in those weighing more than 90 kg. Patients from that study who had involvement of hands, feet, or nails were analyzed in a post-hoc study 51. Altogether, 131 patients were included because of involvement of hands and/or feet, and 304 patients were included because of psoriasis of the fingernails.…”
Section: Efficacy In Trials Of Brodalumab Secukinumab and Ixekizumabmentioning
confidence: 99%
“…The effect of body weight on treatment response rates showed slightly higher PASI 75 responses in patients weighing < 90 kg than in those weighing > 90 kg. Patients from that study who had involvement of hands, feet or nails were analyzed in a post-hoc study [32,33]; 131 patients because of involvement of hands and/or feet, and 304 because of psoriasis of the fingernails. There were clinically relevant improvements in hand and foot involvement after 12 weeks of treatment with secukinumab using the early regimen.…”
Section: Phase II Studiesmentioning
confidence: 99%